RELIGI RUWAT DALAM KIDUNG SUDAMALA - Ria Kasanova (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTJava community has a form of customs that have systems such as values, norms, views and rules of life in society that embodies in the form of traditional ceremonies, to maintain harmony and harmony of the universe. In various forms of traditional ceremonies are still maintained to date, such as the salvation of birth, death, descend, and others. One of the traditional rituals of Javanese society is still done is ruwatan ceremony. Sudamala is a famous ruwat story in the final days of the majapahit kingdom. The method of this research is analytical description method. This study aims to find what is contained in the song Sudamala through data analysis activities followed by then drawn conclusions. Next is to make the tangible text description. Based on the above discussion can be found forms of religious systems that are written in it, namely; religious emotions, belief systems, and religious people.Keywords: religion, ruwat